Excellent photocatalytic performances of Co3O4–AC nanocomposites for H2 production via wastewater splitting. (January 2022) - Sekar, Sankar; Preethi, V.; Saravanan, S.; Kim, Deuk Young; Lee, Sejoon
Abstract: Natural sunlight-driven photocatalytic hydrogen production from wastewater is one of the most desirable techniques that can realize future green energy technology. Herein, we report the synthesis and the characterization of the biomass activated carbon (AC)-decorated cobalt oxide (Co3 O4 ) nanocomposites for solar-stimulated photocatalytic hydrogen production from sulphide wastewater. The Co3 O4 -AC nanocomposites were ultrasonically synthesized by using hydrothermally-grown spinel Co3 O4 nanoflakes and biomass-derived AC nanoflakes. Co3 O4 -AC showed a nanobundle-like aggregated morphology, and exhibited a large specific surface area ( 133 m 2 /g). Through utilizing Co3 O4 -AC as a photocatalyst for photocatalytic splitting of sulphide wastewater (0.2 M) under solar irradiance with 730 W/m 2, an enhanced H2 production efficiency ( 70 mL/h) was achieved owing to the synergic effects from 2-dimentionally configured Co3 O4 and AC microstructures; i . e ., large surface area of Co3 O4 and high electrical conductivity of AC. These findings suggest the nanocomposites of Co3 O4 -AC to hold great promise for the green approach of photocatalytic wastewater splitting. Graphical abstract: Image 1 Highlights: The nanocomposites of Co3 O4 -AC were prepared by ultrasonication of Co3 O4 and AC. Co3 O4 -AC showed an aggregated nanobundle morphology that possesses high porosity. Co3 O4 promotes the photocarrier generation and AC enhances the charge transport. These lead to the highly-efficient photocatalytic hydrogen-production activity. Co3 O4 -AC can be used as a photocatalyst for solar-drivable wastewater splitting.